Digital Literacy and Personal Data Sharing Attitudes: A Study of AI Image Generator Users Among East Java’s Generation Z - Nisrina Maulida Putri; Sumardjijati (International Journal of Social, Economic, and Business, 2026)
The rapid adoption of artificial intelligence image generators among Generation Z introduces significant privacy threats, particularly regarding the collection and exploitation of biometric data. This study aims to examine the correlation between digital literacy levels and personal data sharing attitudes among Generation Z artificial intelligence image generator users in East Java. A quantitative correlational method was utilized with a purposive sample of 126 active users. Data were collected through an online questionnaire utilizing a five-point Likert scale and analyzed using the Pearson Product Moment correlation. The findings reveal a strong and significant negative correlation between digital literacy and personal data sharing attitudes (r = -0.726, p = 0.000). This indicates that higher digital literacy significantly fosters a more protective and cautious attitude toward sharing personal biometric data. Furthermore, the discussion highlights a privacy paradox where users exhibit high affective anxiety toward risks like deepfakes, yet display permissive conative behaviors due to technological determinism and social trends. The study concludes that digital literacy serves as a vital cognitive capacity for managing communication privacy boundaries. The implication of this research emphasizes the necessity for educational institutions and policymakers to design digital literacy programs that go beyond technical access, focusing extensively on critical evaluation and ethical reflection to foster a secure digital ecosystem.